Relationship Between International Trade and Economic Growth: A Case of Ho Chi Minh City - Thi Lai, Nguyen; Thi Anh, Nguyen; Thi Phuong Linh, Phan; Minh Hang, Nguyen (British Journal of Marketing Studies, 2019)
Economic growth has been gradually reduced depending on investment capital, increasing scientific and technical factors. Commercial sector of Ho Chi Minh City (HCMC) continued to grow, total retail sales of goods and service revenue increased higher than the same period. However, the context of 2019, HCMC has facing many problems such as the limitations of investment resources, human resource quality... This requires HCMC must improve the quality of economic growth. Therefore, the objective of this study is to explore the determinants affecting the economic growth of HCMC. The researchers surveyed 400 managers related to exporting enterprise in HCMC. They answered 15 questions and 395 samples processed. The data collected from August 2018 to April 2019 in HCM. Simple random sampling technique. The data analyzed Cronbach's Alpha and the exploratory factor analysis (EFA), which used for Structural Equation Modelling (SEM) technique. Managers’ responses measured through an adapted questionnaire on a 5-point Likert scale. Finally, the findings of the paper have three factors affecting the economic growth of HCMC with significance level 0.01.